Factors associated with return to work in breast cancer survivors treated at the Public Cancer Hospital in Brazil - Colombino, Isabela Caroline Freitas; Sarri, Almir José; Castro, Isabela Queiros; Paiva, Carlos Eduardo; da Costa Vieira, René Aloisio [UNESP] (Springer Nature, 2020)
Purpose: To evaluate the impact of return to work on the quality of life of breast cancer patients and to identify factors related to nonreturn to work. Methods: An observational, cross-sectional study was performed in breast cancer survivors who had worked before their breast cancer diagnosis. We evaluated factors related to return to work (patient perspective, disease, and work), EORTC quality of life questionnaires (general: EORTC QLQ-C30; and breast cancer-specific: EORTC QLQ-BR23), the Shoulder Pain and Disability Index (SPADI), and the Anxiety and Depression Scale (HADS). Half of the patients underwent a physical therapy examination (shoulder goniometry, hand dynamometry, and limb volume). Univariate and multivariate analysis were performed. Results: We included 304 patients, 163 of whom underwent physiotherapy evaluation. Approximately 54.0% (164) of the patients returned to work after treatment. The women who returned to work presented lower age, higher education levels, higher incomes, and smaller initial tumor size. The women who returned to work had higher scores related to body image and sexual function, lower scores in relation to disability and pain, and lower scores related to anxiety and depression. In the multivariate model to evaluate nonreturn to work, pretreatment variables were age, education level, and clinical staging. Sequelae related to loss of strength increased the risk of nonreturn to work. Conclusion: Return to work was influenced by age, education level, previous activity types, axillary treatment, and physical sequelae related to loss of hand strength. Breast cancer treatment decreased the women’s work capacity. Return to work improved the patients’ quality of life.
Keywords: Breast neoplasms; QoL; Return to work; Women, working; Work capacity evaluation